Effects of additional rifle-carriage training on physiological markers and roller-skiing performance in well-trained biathletes - Jonsson Kårström, M.; McGawley, K.; Laaksonen, M. S. (Journal of Science in Sport and Exercise, 2021)
Purpose: The purpose was to investigate whether an increased amount of training while carrying the rifle affects skiing in well-trained biathletes at submaximal and maximal workloads during a pre-season period lasting a minimum of 12 weeks. Methods: Seventeen well-trained biathletes (9 females, 8 males) were assigned to an intervention (IG, n = 10) or control (CG, n = 7) group. Before (T1) and after (T2) the training intervention all participants performed, using treadmill roller-skiing, a submaximal test without the rifle on one day and two submaximal workloads and a maximal time trial (TT) with the rifle on a subsequent day. Between T1 and T2 all participants performed a minimum of 12 weeks of normal training, the only difference between groups being that IG performed more of their training sessions carrying the rifle. Results: IG performed more training compared to CG (15.4 ± 1.1 vs. 11.2 ± 2.6 h/week, P < 0.05), including a higher amount of training with the rifle (3.1 ± 0.6 vs. 1.1 ± 0.3 h/week, P < 0.001). Speed at 4 mmol/L of blood lactate increased significantly for CG from T1 to T2 (P = 0.028), while only tended to increase for IG (P = 0.058). Performance during the TT, VO2max and the aerobic metabolic rate increased significantly from T1 to T2, although the differences disappeared when including the speed at baseline as a covariate. Conclusion: According to the present results, increasing training while carrying the rifle by 2 h/week does not appear to improve skiing performance in well-trained biathletes. In addition, physiological markers at submaximal and maximal intensities while carrying the rifle were not affected after the training intervention.